The Multiple Roles of Imidazolium Ionic Liquids in Transition‐Metal Catalysis: The Palladium‐Catalyzed Telomerization of 1, 3‐Butadiene with Acetic Acid. Issue 6 (2nd March 2015) - Balbino, João M.; Peral, Daniel; Bayón, J. Carles; Dupont, Jairton
Abstract The telomerization of 1, 3‐butadiene with acetic acid catalyzed by palladium(II) acetate associated with a series of phosphines in 3‐(2‐methoxyethyl)‐1‐methylimidazolium acetate was used to investigate the role of the ionic liquid. The ionic liquid plays multiple roles in this reaction as it acts as the solvent, stabilizer, ligand, and cocatalyst. The reaction performed in the presence of Dan2phos, a trifluoromethylated sulfonated triarylphosphine, at 100 °C for 24 h gave a turnover number of 14 600 with 89 % selectivity to telomers at 75 % 1, 3‐butadiene conversion and complete acetic acid conversion.